Research of authentication techniques for the Internet of things - Hongqiang YAN; Linjie WANG (Tongxin xuebao)
Identity authentication technology is a key technology in the Internet of things (IoT)security field which ensures the authenticity of the identity information of users and device nodes connected to the IoT.Due to the low cost,low power consumption,small storage of IoT devices and heterogeneity of IoT network,the identity authentication mechanisms in traditional computer networks are often not applicable.Firstly,the development process of IoT was introduced,the security risks of IoT and the challenges faced by the authentication work were analyzed.Then the emphasis was put on comparison of the advantages and disadvantages among five typical authentication protocols.Moreover,the authentication technologies in several practical scenarios of RFID,smart grid,Internet of vehicles,and smart home were summarized and analyzed.Finally,the future research direction was discussed.